Analysis of Land Surface Temperature Changes in Sorong City, Indonesia Using Landsat 8 Satellite Image Data Based on Cloud Computing - Rakuasa, Heinrich; Do Huy-Hoang; Rafly Aulya Rizky Nasution; Fadlan Turi; Muh Hidayatullah (Journal of International Multidisciplinary Research, 2024)
This study aims to analyze land surface temperature changes in Sorong City, Indonesia using Landsat 8 satellite image data and Google Earth Engine cloud computing platform. With rapid urbanization, understanding the dynamics of surface temperature is important. Through satellite imagery and cloud computing technology, this analysis provides accurate monitoring of temperature change, supports climate change mitigation strategies, and designs more sustainable cities.